Exploring Transformative Pedagogy in Teaching Mathematics - Shrestha, Indra Mani; Luitel, Bal Chandra; Pant, Binod Prasad (Mathematics Education Forum Chitwan, 2020)
This paper is based on the first author’s auto/ethnographic inquiry into pedagogical practices based on his MPhil dissertation. The second author being the dissertation supervisor has played a facilitative role in developing the structure and content of the paper while the third author has provided critical comments and inputs on overall aspects of the paper. Various research studies show that teaching mathematics has been a challenging task for many teachers in Nepal. Based on our experience, most of the mathematics teachers including the first author are found struggling for improving their pedagogical skills to provide students with meaningful (authentic, empowering, justifiable and inclusive) learning. In so doing, instead of looking into their ‘inner-selves”, they oftentimes wander around the outer world seeking the better (and the best) possible pedagogical approaches. In this orientation, as an auto/ethnographer, the first author narrates his stories on pedagogical practices to examine his traditional teacher-centric pedagogical practices and explore the transformative pedagogy as student-centric pedagogy. The study helped him improve his pedagogical practices and envision a synergy of teacher-centric pedagogy and transformative pedagogy in his professional life-world. Therefore, this paper aims at sharing the research context, theoretical position, methodology, and reflection and lessons learned. This paper is developed from the perspective of the first author’s experience using the first person “I”.